2018
DOI: 10.1111/jch.13253
|View full text |Cite
|
Sign up to set email alerts
|

The risk of hypertension and cardiovascular disease in women with uterine fibroids

Abstract: Women with fibroids have a notably high hypertension risk. However, adjusted data regarding other cardiovascular disease (CVD) risk factors are scarce. In this cross-sectional study, CVD risk factors, hemodynamic parameters, and asymptomatic organ damage were analyzed between women with uterine fibroids and controls in a multi-ethnic population. In total, 104 women with self-reported fibroids and 624 controls were included. Women with fibroids had significantly higher odds to have hypertension (OR 3.4; 95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 46 publications
(103 reference statements)
4
48
1
2
Order By: Relevance
“…Several epidemiological studies have been performed to examine the association of obesity with the risk of UFs in premenopausal women with inconsistent findings. 12–33 Some studies reported a positive association between obesity and the risk of UFs, 12–25 32 33 while others showed non-significant association. 26–31 To address the lack of consensus in the literature, we performed a systematic review and meta-analysis of observational studies to quantitatively evaluate the association of obesity with the risk/prevalence of UFs.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have been performed to examine the association of obesity with the risk of UFs in premenopausal women with inconsistent findings. 12–33 Some studies reported a positive association between obesity and the risk of UFs, 12–25 32 33 while others showed non-significant association. 26–31 To address the lack of consensus in the literature, we performed a systematic review and meta-analysis of observational studies to quantitatively evaluate the association of obesity with the risk/prevalence of UFs.…”
Section: Introductionmentioning
confidence: 99%
“…Excluding hypertension, Haan and associates did not find a correlation between UF and other factors linked to cardiovascular risk, but this finding could be related to the concomitant treatment of hypertension or to the heterogeneity of UF and of patients’ age.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, angiotensin II‐induced proliferation of leiomyoma cells has been shown, and the significant role of angiotensin II in the pathogenesis of hypertension, both directly inducing vasoconstriction and indirectly stimulating aldosterone synthesis, is well known. Considering the increased hypertension risk reported by Haan and colleagues in women with UF, the involvement of the RAAS could explain a pathophysiology common to these 2 conditions. Because ACE inhibition as well as AT1R blockade have been shown to inhibit tumor angiogenesis, tumor growth, vascular density, mitotic index, and cell proliferation, ACE‐inhibitors and AT1R blockers could be used to prevent or reduce tumor development in susceptible subjects bearing these polymorphisms.…”
Section: Angiotensin II and Aldosterone Commitment In Ufmentioning
confidence: 95%
See 1 more Smart Citation
“…These in vitro studies suggest a possible use of MR blockers in the treatment of UF; however, only eplerenone could be considered, because of the frequent metrorrhagia associated with SP (47). Recently a higher risk of hypertension has been reported in patients with UF (56). However, a previous study evidenced that hysterectomy did not influence the risk of hypertension and on the contrary it was associated with long-term increase of cardiovascular risk (57).…”
Section: Aldosterone and Uterine Fibroidsmentioning
confidence: 99%